1985
DOI: 10.1177/002205748516700302
|View full text |Cite
|
Sign up to set email alerts
|

Connected Education for Women

Abstract: We present a model of education, called “connected education,” designed to be appropriate for women, and derived from interviews with 135 women, varying widely in age, social and ethnic background, and educational institution. We explore four features of the model: (a) explicit confirmation for modes of thinking and kinds of knowledge that women value; (b) opportunities to explore the particularities of firsthand experience, before moving to conceptualization of that experience; (c) support for women's efforts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…The most useful heuristic seems to have been the distinction between separate knowing and connected knowing, which has served as a means for understanding gender-related approaches to learning. The authors of the study have provided suggestions on both connected education for women and connected teaching, which have been adapted at the classroom and institutional level (Belenky et al, 1986;Clinchy, 1990;Clinchy, Belenky, Goldberger, & Tarule, 1985). They advocate a model of teachers as "participant-observers" who model and display their thinking processes in public dialogue, a classroom culture that accepts the voicing of uncertainty, standards of evaluation that are coconstructed by teachers and students, and classes in which knowledge is created not through conflict but consensus.…”
Section: Discussionmentioning
confidence: 99%
“…The most useful heuristic seems to have been the distinction between separate knowing and connected knowing, which has served as a means for understanding gender-related approaches to learning. The authors of the study have provided suggestions on both connected education for women and connected teaching, which have been adapted at the classroom and institutional level (Belenky et al, 1986;Clinchy, 1990;Clinchy, Belenky, Goldberger, & Tarule, 1985). They advocate a model of teachers as "participant-observers" who model and display their thinking processes in public dialogue, a classroom culture that accepts the voicing of uncertainty, standards of evaluation that are coconstructed by teachers and students, and classes in which knowledge is created not through conflict but consensus.…”
Section: Discussionmentioning
confidence: 99%
“…Much research has been conducted examining gender differences in epistemic beliefs (e.g., Baxter Magolda, 1992;Belenky, Clinchy, Goldberger, & Tarule, 1986;Chen & Pajares, 2010;Clinchy, Belenky, Goldberger, & Tarule, 1985). These studies have shown mixed resultssome finding gender differences and others showing none.…”
Section: Group Differences In Implicit Theories Of Ability and Epistementioning
confidence: 99%
“…Pamela's opinion is supported by research reported by Gilligan (1982) indicating that females approach problem solving from the perspective of interdependence and relationships, whereas males approach problem solving from an isolated skills analysis point of view. Clinchy, Belenky, Goldberger, and Tarule (1985) reported that Women want and need an education in which connection is emphasized over separation, understanding and acceptance over judgment and assessment, and collaboration over debate. They need a curriculum which accords respect to and allows time for the knowledge that emerges from first-hand experience.…”
Section: Enactment Of Plans/observation/initial Reflectionsmentioning
confidence: 99%